An Examination of Occupational Therapy Telehealth Service Delivery Among Novice Users During the COVID -19 Pandemic - Breeden, Lori E.; Tyger, Hannah; Reckers, Alexandra M.; Johnson, Megan; Morales, Analicia M.; Ober, Lauren; Williams, Mackenzie A. (International Journal of Telerehabilitation, 2023)
The COVID -19 pandemic allowed for widespread implementation of telehealth as a delivery method for occupational therapy (OT) services. The purpose of this study was to investigate the perceptions of novice telehealth OT practitioners regarding telehealth as a delivery method for OT services. Quantitative data was collected through a modified version of the Telehealth Usability Questionnaire and analyzed via descriptive statistics. Qualitative data was collected by open-ended questions and analyzed via thematic analysis. OT practitioners’ responses revealed four major themes: logistics of telehealth practice, role of client champions, capacity of the OT practitioner, and styles and approaches. The study revealed that OT sessions delivered via telehealth increased access to clients and continuity of services. Client champion engagement, effective coaching strategies, and practitioner flexibility supported the success of OT telehealth sessions.